The Relationship of Mutualism Between the Diversity of Gut Bacteria Metabolism and The Human Body: A Review - Utama, Alifka Fajri; Adiningsih, Arin Sucia; Milasari, Azizah Eka; Cahyarani, Reihana Marsha; Rahayu, Tiara; Fendiyanto, Miftahul Huda; Satrio, Rizky Dwi (MUNISI: Military Mathematics and Natural Sciences, 2023)
Do you know the relationship of mutualism between the diversity of gut bacteria metabolism and the human body? Hearing bacteria our thinking is directed to something that pathogenic and parasitic to the host, not all bacteria can cause disease. Precisely the human body has a mutual relationship between gut bacteria and human metabolism such as helping in the digestive process of both coarse fiber, protein, fat, detoxifying toxins as well as endurance and maintaining homeostatic. The understanding of the mechanism of homeostatic gut bacteria is not fully known especially until the basic genetics and metabolism in each of these gut bacteria. This paper is expected to improve understanding of the interaction of intestinal bacteria such as Bacteroides, Bifidobacterium, Escherichia coli, Lactobacillus, and Saccharomyces boulardii to human metabolism, especially in detecting diseases and improving the health of the body. The focus of this paper is on the diversity of bacterial metabolic pathways in the human gut as well as the influence of the presence of such bacteria in the body. The studies was completed by study libraries with qualitative and quantitative data.